The World as Abyss The Caribbean and Critical Thought in the Anthropocene - Pugh, Jonathan (University of Westminster Press, 2023)
This book is about a distinctive 'abyssal' approach to the crisis of modernity. In this framing, influenced by contemporary critical Black studies, another understanding of the world of modernity is foregrounded - a world violently forged through the projects of Indigenous dispossession, chattel slavery and colonial world-making. Modern and colonial world-making violently forged the 'human' by dividing those with ontological security from those without, and by carving out the 'world' in a fixed grid of space and time, delineating a linear temporality of 'progress' and 'development'. The distinctiveness of abyssal thought is that it inverts the stakes of critique and brings indeterminacy into the heart of ontological assumptions of a world of entities, essences, and universal determination. This is an approach that does not focus upon tropes of rescue and salvation but upon the generative power of negation. In doing so, it highlights how Caribbean experiences and writings have been drawn upon to provide an important and distinct perspective for critical thought. "How is it that ontology has come to be seen as the antidote for modernity? While Foucault denigrated ontology as a mistaken and parochial exercise, contemporary social theory holds out the promise that new modes of planetary knowledge will save us from our own excesses. Drawing together long traditions in Caribbean scholarship with Afro-pessimist thought, Pugh and Chandler illustrate how the search for more emancipatory ontologies - relational ontologies, indigenous ontologies, non-human ontologies, etc. - not only misunderstands the problem of modernity but (more importantly) works to veil the negative force that marks both the limit and cause of all such knowledge practices: what they term the abyss. To engage in abyssal thought - as they lay out - is to inhabit a site of refusal: a determination not to be drawn into the lure of ontological 'correction' and to recognise that the practice of world making cannot not bear the imprint of colonial violence. Articulated in passionate declarative prose, these authors powerfully illuminate the trap of the emancipatory instinct and the promise of a deconstructive ethic." - Mitch Rose, Senior Lecturer in Human Geography, Aberystwyth University, UK "A much-needed intellectual effort in the non-reductionist and non-essentialising style of Pugh and Chandler's previous book. The World as Abyss gives Caribbean thought and culture the place they deserve within critical theory and materialist studies." - Mónica Fernández Jiménez, Valladolid University, Spain "For some time now scholars have questioned the overly general assumptions about the 'anthropos' of the Anthropocene, but much work needs to be done to flesh out what a decolonized Anthropocene might be. Pugh and Chandler's The World as Abyss provides an original, intriguing and compelling counterpoint to bland Anthropocene humanism (and posthumanism). This timely work explores the poetics of the Caribbean and provides a way to think about the Anthropocene and the future beyond the managerialism of the present. This book is essential reading for those working in the environmental humanities or Anthropocene studies." - Claire Colebrook, Professor, Penn State University, USA "This book names an apocalypse that began long ago. Pugh and Chandler patiently follow the journey of thought as it travels from the Middle Passage to the Caribbean. This brings them face-to-face with the horror of anti-Black violence, not as just another resource to strip-mine, but as an unavoidable abyss that confines all thought. Its reminder: that we have still not yet begun to think a truly Black world." - Andrew Culp, Professor, California Institute of the Arts, USA "With the force of a manifesto, the intensity of a polemic, and the nuance of a treatise, this book sets out to disavow the disavowal of Colonial violence in the making of the contemporary world and thought. Learning from Caribbean thinkers, writers, and poets, it sets to work unworking, desedimenting and deconstructing, the violent ontological foundations by which anti-Black worlds maintain and reproduce their innocence and ignorance. Replaying and reiterating, extending and multiplying, gestures of refusal - refusals of subjection, of History, of Geography, of meaning, of Being - there is the refusal of the World as it is and of the World as it could be. The World as Abyss artfully combines a critique of the historical forces which make and unmake the contemporary moment with the suspension of horizons, of ends, of grounds. What emerges in the wake is an intensification of the generative capacity of this refusal; voids, arrhythmia, counter-times, displacements, dislocations, the abyssal. First as threat and then as promise" - Paul Harrison, Associate Professor of Human Geography, Durham University, UK